Effectiveness of adding inspiratory muscle training to a cardiac rehabilitation program in people with acute myocardial infarction revascularized by percutaneous coronary intervention (CARDIOINSPIRE): Study protocol for a randomized controlled trial - Jose M. Zuazagoitia-Lama-Noriega; A. M. Gómez-González; Jose A. Moral-Munoz (PLoS ONE, 2026)
Objectives This study aims to analyze the effectiveness of adding inspiratory muscle training (IMT) to a cardiac rehabilitation program (CRP) in people with acute myocardial infarction (AMI) revascularized by percutaneous coronary intervention (PCI) after 16 sessions. The biopsychosocial profile and the sex differences of this population will also be evaluated. Design Triple-blind, parallel-group, low-risk randomized controlled trial. Methods 72 patients diagnosed with AMI will be enrolled and randomly assigned to two groups. The control group will complete the usual CRP with the addition of IMT at 5% of the maximal inspiratory pressure (MIP) (sham load). The intervention group will perform the same CRP but will add an IMT program at 70% of MIP. Outcomes will be collected at baseline and post-intervention. The main outcome will be cardiorespiratory fitness (CF) measured in metabolic equivalent of task (MET), secondary outcomes will be MIP, maximal expiratory pressure, peripheral muscle strength, dyspnea, social support, anxiety, depression, coping with the disease, sexual dysfunction, quality of life (QoL), sleep quality, eating habits, and body composition. Descriptive statistics will summarize baseline data, and influential outliers will be managed via winsorization or exclusion, confirmed by sensitivity analyses. A mixed-design ANOVA will evaluate differential changes over time. Depending on attrition rates, missing data will be addressed using either complete case analysis (<5%) or multiple imputation with an intention-to-treat approach (>5%). Discussion According to recent literature, improvements in CF and MIP are expected. For the rest of the outcomes, data are currently limited, inconclusive or lacking. We hypothesize that changes in CF may affect the rest of the outcomes and, in our opinion, IMT at 70% of the MIP will significantly improve CF. Clinical implications If the expected benefits are observed, the results may recommend including IMT as a fundamental component of a CRP in our study population. Trial registration number Registered prospectively at ClinicalTrials.gov ( NCT06681740 ) Version 4.